Rancang Bangun Aplikasi E-Learning Berbasis Multiplatform untuk Mata Pelajaran Bahasa Indonesia dengan Menggunakan Pendekatan Technology Acceptance Model (TAM) - Titus Kristanto; Rinci Kembang Hapsari; Vinda Setia Nita; Siti Maimunah (Jurnal Teknik Informatika dan Sistem Informasi, 2015)
Indonesian Language Lessons for 2nd grader of Elementary School with Standard of Competency 4 is the subject to discuss writing of short story with the correct words, capital words usage and the usage of correct full stop marker in the upright continued writing letters. The multiplatform application design is to seek solutions to problem learning method less attractive. This applications are operated in three operating systems, Windows, Android, and Ubuntu. This research employes approach of Technology Acceptance Model (TAM) by involving teachers and 2nd graders from Medalem II Public Elementary School in Tuban and Bangah 1 Public Elementary School in Sidoarjo. The data in research were colleted using questionnaires. In addition to using questionnaires, tests were conducted by giving Pre-Test and Post-Test that was, aimed at determininge the differences between the values obtained from the students before and after using the application.Â Keywords â€” E-Learning, Indonesian Language Lessons, Technology Acceptance Model